2017
DOI: 10.2147/copd.s126400
|View full text |Cite
|
Sign up to set email alerts
|

Mid-regional pro-adrenomedullin and copeptin to predict short-term prognosis of COPD exacerbations: a multicenter prospective blinded study

Abstract: BackgroundExacerbations of COPD (ECOPD) are a frequent cause of emergency room (ER) visits. Predictors of early outcome could help clinicians in orientation decisions. In the current study, we investigated whether mid-regional pro-adrenomedullin (MR-proADM) and copeptin, in addition to clinical evaluation, could predict short-term outcomes.Patients and methodsThis prospective blinded observational study was conducted in 20 French centers. Patients admitted to the ER for an ECOPD were considered for inclusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Biomarkers are invariably associated with adverse outcomes, the strength of association influenced by population, comorbidities, inclusion/exclusion criteria, follow-up period, outcome studied, and adjustment methods. In the current and most previous studies, the lack of blinded endpoint adjudication using standardised criteria represents a major limitation in correlating biomarkers with cardiac specific outcomes and mortality [19,22,23]. In the present study, all biomarkers displayed similar AUCs for predicting 30-day mortality to the CURB-65 score.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…Biomarkers are invariably associated with adverse outcomes, the strength of association influenced by population, comorbidities, inclusion/exclusion criteria, follow-up period, outcome studied, and adjustment methods. In the current and most previous studies, the lack of blinded endpoint adjudication using standardised criteria represents a major limitation in correlating biomarkers with cardiac specific outcomes and mortality [19,22,23]. In the present study, all biomarkers displayed similar AUCs for predicting 30-day mortality to the CURB-65 score.…”
supporting
confidence: 48%
“…Further, recently, a multicentre study has developed a novel, simplified, prognostic tool for COPD, independent of lung function, and copeptin was included among the independent predictors of long-term mortality [23]. Interestingly, a French study including 277 patients hospitalised for acute exacerbation of COPD reported opposite results, as copeptin levels were not independently related to 30-day outcomes, including death; however, in the same cohort, copeptin was independently associated with 7-day death/need for ICU [22]. Thus, the debate on the utility of copeptin in acute exacerbation of COPD is actual and ongoing.…”
mentioning
confidence: 99%
“…Finally, a newly published multicenter study of AECOPD patients did not find any association between copeptin and a short-term (30 days) composite outcome that included mortality, transfer to the intensive care unit, or a new visit to the emergency room. Notably, patients who required immediate intensive care unit monitoring and/or assisted ventilation (invasive or non-invasive) were excluded from the study and only 14 of 277 included patients died [ 30 ]. To clarify the prognostic properties of copeptin with respect to mortality in COPD in the acute setting we categorized unselected patients with acute dyspnea by established guidelines under the scrutiny of two experts working independently and analyzed the prognostic properties of copeptin in AECOPD and acute HF separately.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the promising results of recent studies focused on the diagnostic and prognostic role of copeptin in the setting of acute dyspnea-related both to heart failure [ 10 12 ] and acute exacerbations of chronic obstructive pulmonary disease [ 10 , 11 , 13 ]; the findings in the field of hyponatremia are more controversial.…”
mentioning
confidence: 99%